Restrição de crédito e decisão de investimento: evidências de racionamento de crédito ao setor informal da economia brasileira - Arthur de Rezende Pinto (2010)
This paper investigates the existence of credit rationing to informal enterprises in the Brazilian economy. A model of occupational choice developed in Evans and Jovanovic (1989) is adapted for the firm's investment decision, conditional on its budget constraint. One result of this model is that wealth enhances investment particularly in more credit constrained firms. This result motivates our empirical strategy that uses the relationship between wealth and investment to identify whether urban informal enterprises are credit constrained. To mitigate the problem of endogeneity between wealth and investment, we considered only the young enterprises, i.e. those with less than five years of existence, given that these firms have not yet accumulated enough wealth to generate a reverse causality. Using data from the Economia Informal Urbana survey (ECINF) conducted by IBGE, for the year 2003, we find evidence that wealth has a significant impact on various investment decisions, marginal effects ranges from 0.002 to 0.03. Furthermore, our estimates suggest that self-employed workers face stronger credit restrictions than employers. Overall, our results corroborates the previous findings of empirical literature.